Pengaruh Media Sosial terhadap Perilaku Kriminal Remaja di Indonesia - Chiara Belva Chatlina; Kuswandi Kuswandi (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2025)
The development of social media as part of digital technology has significantly transformed patterns of social interaction among adolescents in Indonesia. Social media no longer functions solely as a medium for communication and self-expression, but also as a social space that influences behavioral formation, including deviant and criminal behavior. This study aims to analyze the influence of social media on juvenile criminal behavior from a criminological perspective, with particular attention to social learning processes and the weakening of social control in digital environments. This research employs a qualitative method using a literature study approach by examining scientific journals, official reports, and statistical data related to social media use and adolescent behavior. The findings indicate that high intensity of social media use, exposure to negative content, and the normalization of aggressive behavior in digital spaces contribute to increased vulnerability of adolescents to criminal behaviors such as cyberbullying, online aggression, and other forms of deviance. Within the framework of Social Learning Theory, social media serves as a medium for behavioral learning through mechanisms of observation, imitation, and social reinforcement, while Social Control Theory highlights how weak supervision by families and educational institutions amplifies the risk of deviant behavior. The implications of this study emphasize the importance of preventive, non-penal approaches through strengthening social control, improving digital literacy, and enhancing the active role of families and schools to minimize the risk of juvenile criminal behavior in the digital era.